Pengembangan Media Pembelajaran Berbasis Flash pada Mata Pelajaran Rancang Bangun Jaringan Kelas XII Jurusan TKJ SMKN 2 Malang dengan Model Pengembangan Four-D - Hakky Affandy Latief; Admaja Dwi Herlambang; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
When the learning process in the learning media class can help teachers when delivering material. But there are problems during the implementation of the learning process that is the absence of learning media used by the teacher, the material obtained by students comes from the internet and students search for material independently so as to result in low student learning outcomes or under the KKM. Based on the problems identified, this study has the aim of developing flash-based media or learning resources. Development of media or learning resources using the Four-D model, this model has four stages, namely the Define, Design, Develop, and Disseminate stages. Data collection techniques used were interviews, tests, and questionnaires. The results of the validation test from material experts and media experts stated that flash-based learning media were valid and appropriate to use when used for the learning process with a percentage value of 94.11% for the validity level of the material and included in the "Very Good / Valid" category, then the results of Media experts show a percentage of 90.78% and fall into the category of "Very Good / Valid". The results of the average value of the pre-test and post-test were 46.75 and 80.11. The results of the t-test show that the significance value <0.05 is equal to 0.00 from the results. It can be concluded that there is a differentiation between the value of pre-test and post-test and the flash-based learning media that have been developed effectively used in the learning process. This is indicated by the results of the pre-test and post-test scores that have increased and the significance values ​​produced.